2006
DOI: 10.1105/tpc.105.038240
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Male Sterility of Rice with Boro II Cytoplasm Is Caused by a Cytotoxic Peptide and Is Restored by Two Related PPR Motif Genes via Distinct Modes of mRNA Silencing

Abstract: Cytoplasmic male sterility (CMS) and nucleus-controlled fertility restoration are widespread plant reproductive features that provide useful tools to exploit heterosis in crops. However, the molecular mechanism underlying this kind of cytoplasmicnuclear interaction remains unclear. Here, we show in rice (Oryza sativa) with Boro II cytoplasm that an abnormal mitochondrial open reading frame, orf79, is cotranscribed with a duplicated atp6 (B-atp6) gene and encodes a cytotoxic peptide. Expression of orf79 in CMS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
564
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 594 publications
(594 citation statements)
references
References 59 publications
10
564
1
4
Order By: Relevance
“…I observed that the Rf-1 gene was more or less effective on both cytoplasm types: the Rf-1 derived from IR36 restored pollen fertility in a gametophytic manner in BT-type CMS (Table 1), and partially restored pollen fertility in WA-type CMS (Table 2). These results are consistent with those obtained in previous studies using indica and japonica varieties (Young and Virmani 1984, Raj and Virmani 1988, Bharaj et al 1991, 1995, Teng and Shen 1994, Yao et al 1997, Akagi et al 2004, Komori et al 2004, Wang et al 2006. At present, it is remains to be determined whether the partial restoration of pollen fertility in WA-type CMS is a pleiotropic effect of Rf1a or Rf1b (Wang et al 2006), or is due to the clustering of multiple Rf genes of the Rf-1 locus.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…I observed that the Rf-1 gene was more or less effective on both cytoplasm types: the Rf-1 derived from IR36 restored pollen fertility in a gametophytic manner in BT-type CMS (Table 1), and partially restored pollen fertility in WA-type CMS (Table 2). These results are consistent with those obtained in previous studies using indica and japonica varieties (Young and Virmani 1984, Raj and Virmani 1988, Bharaj et al 1991, 1995, Teng and Shen 1994, Yao et al 1997, Akagi et al 2004, Komori et al 2004, Wang et al 2006. At present, it is remains to be determined whether the partial restoration of pollen fertility in WA-type CMS is a pleiotropic effect of Rf1a or Rf1b (Wang et al 2006), or is due to the clustering of multiple Rf genes of the Rf-1 locus.…”
Section: Discussionsupporting
confidence: 82%
“…These results are consistent with those obtained in previous studies using indica and japonica varieties (Young and Virmani 1984, Raj and Virmani 1988, Bharaj et al 1991, 1995, Teng and Shen 1994, Yao et al 1997, Akagi et al 2004, Komori et al 2004, Wang et al 2006. At present, it is remains to be determined whether the partial restoration of pollen fertility in WA-type CMS is a pleiotropic effect of Rf1a or Rf1b (Wang et al 2006), or is due to the clustering of multiple Rf genes of the Rf-1 locus. Nucleotide sequencing of the Rf-1 locus revealed that it consists of multiple PPR protein genes, a gene family to which most of the plant Rf genes belong (Bentolila et al 2002, Koizuka et al 2003, Brown et al 2003.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations